2015
DOI: 10.2214/ajr.14.13448
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Maximum Shear-Wave Stiffness of Breast Masses as a Predictor of Histopathologic Severity

Abstract: Despite overlap in Emax values, maximum stiffness measured by SWE is a highly effective predictor of the histopathologic severity of sonographically depicted breast masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 32 publications
(45 reference statements)
9
47
3
2
Order By: Relevance
“…Results have consistently shown that high‐grade tumors tend to have greater stiffness on elastography. The maximum stiffness of IDC has been shown to be greater than that of DCIS in previous studies; tumors tend to become stiffer as they grow because of the increase of fibrosis and decrease of necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Results have consistently shown that high‐grade tumors tend to have greater stiffness on elastography. The maximum stiffness of IDC has been shown to be greater than that of DCIS in previous studies; tumors tend to become stiffer as they grow because of the increase of fibrosis and decrease of necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Tumor stiffness, assessed with ultrasound elastography or atomic force microscopy appears to increase with increasing grade [91] and predicts poorer prognosis [92]. SPARC/ OSTEONECTIN Microarray for 7 genes which correlate with SPARC 1729 systemically untreated patients from previously published datasets SPARC tends to be highest in luminal-A type, followed by luminal-B followed by basal [63] High SPARC predicts worse survival in HER2 þ, and basal cancers Furthermore, successful chemotherapy decreases tumor stiffness whereas stiffening is observed in chemotherapy-resistant tumors stiffen after treatment [93].…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%
“…SWE has been used to evaluate liver stiffness and stiffness of breast (13,14), prostate (15,16), and thyroid lesions (17). SWE seems to increase specificity and positive predictive value in the assessment of breast (18,19) and prostate lesions (15).…”
Section: Introductionmentioning
confidence: 99%